In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis

Influence of filler size and morphology in controlling the thermal emissivity of aluminium/polymer composites for space applications - Babrekar, Harshada A.; Kulkarni, Naveen V.; Jog, Jyoti Prakash; Mathe, Vikas L.; Bhoraskar, S. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The paper has addressed the problem of controlling the thermal emissivities from metal/polymer composites prepared by solution method. Aluminium is used as a filler and polystyrene as a polymer-matrix. Aluminium particles, with micrometer and nanometer dimensions having different morphologies, were employed. The values of emissivities were reduced when the coarse grains and flakes of aluminium were used as fillers, whereas, no significant change was observed when nano-aluminium was used in the composite. Dielectric dispersion for the composites was measured and the results are analysed in view of Fresnel relation. The differences in the values of dielectric constants, between the experimentally measured and those which can be predicted theoretically, are thought to arise from the interfacial polarization. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Camouflaging; Composite; dielectric constant; Infra-red; Thermal emissivity